Scope and Utility of Ayurveda in Rural and Primary Health Care - Kushwaha, Ashwini Kumar (International Research Journal of Ayurveda & Yoga, 2022)
The population of India is 1.38 billion, of which 65.07% live in rural areas. Health care injustice is a universal phenomenon in rural India and the condition of rural and primary health care in India remains unsatisfactory even after 75 years of independence. Modern health facilities are very poor in rural areas and about 65% of the population lives in rural areas, using Ayurveda and medicinal plants as their primary health care needs. The holistic approach of Ayurveda can provide most of the health services in rural India from its own resources such as preventive and promotive health care. Non-pharmacological remedies of Ayurveda like Sadvritta and Swasthyavritta, Achara Rasayana and Yoga and the use of kitchen spices and common medicinal plants available in rural areas are better alternatives to primary health care in rural areas.